UNDERGRADUATE STUDENTS' PERCEPTION ON USING CHATGPT FOR IDEA DEVELOPMENT IN ACADEMIC WRITING BASED ON TAM: A DESCRIPTIVE STUDY - Muhammad Fadli Alghifari; Sumarni; Eni Rosnija (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores undergraduate students' perceptions of using ChatGPT to help develop ideas in academic writing, based on the Technology Acceptance Model (TAM). The research involved 23 fourth-semester students from the English Education Study Program at Universitas Tanjungpura who had completed a Paragraph Writing course. A descriptive quantitative method was used, and data were collected through a close-ended questionnaire referring to four TAM constructs: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), and Behavioral Intention to Use (BIU). The results showed that students viewed ChatGPT as a helpful and easy tool for generating, organizing, and improving their writing ideas. Most participants had a positive attitude toward ChatGPT and planned to use it again in the future. These findings are relevant to the TAM theory and confirm the importance of usefulness and ease of use in technology acceptance. Unlike previous studies that focused on general writing performance, this study highlights idea development as a key benefit. The findings suggest that ChatGPT is capable of supporting students in writing activities, but further research is needed to explore its long-term impact.